The power of Logos in human rationality and its relevance in the modern era of science - tampilang, risno (KAMASEAN: Jurnal Teologi Kristen, 2024)
The concept of the Logos in the Gospel of John has long been the subject of theological and philosophical discussions. In the era of modern science, questions have arisen about the relevance and relationship between this concept of the Logos and the development of science and human rationality. A hermeneutical approach is used to interpret the meaning of the Logos in historical and contemporary contexts. This study aims to explore the relationship between the concept of the Logos in the Gospel of John and the development of modern science, and to analyze how this understanding can bridge the gap between faith and rationality. The Logos in the Gospel of John is understood as the creative and rational principle underlying the universe, which is also manifested in Jesus Christ. There is a parallelism between the function of the Logos in creation and the role of human rationality in the development of science. The concept of the Logos offers a framework for integrating scientific progress with spiritual wisdom. This view challenges the dichotomy between science and faith, proposing that both realms an complement each other in understanding reality. The concept of the Logos in the Gospel of John has significant relevance in the era of modern science. It offers a holistic perspective that allows for the integration of scientific and spiritual understanding, encouraging a more comprehensive approach to knowledge and reality. This understanding has the potential to bridge the gap between faith and rationality, paving the way for a more constructive dialogue between religion and science.